Comparação entre dreno de sucção, pontos de adesão e cola de fibrina na prevenção de seroma em abdominoplastias - Bercial, Marcos Eduardo [UNIFESP] (2011)
BACKGROUND: Seroma formation is one of the most frequent complications in abdominoplasty. The ultrasound made in abdominal walls is one of the best non-invasive methods to diagnose seroma. There is no evidence wich the best strategy in world literature. OBJECTIVE: This research investigated the formation of seroma in patients that have undergone abdominoplasties using three different methods: a vacuum suction drain, quilting suture and human fibrin sealant. METHOD: Between March and October 2008, 43 abdominosplasties were made in female patients. The sample was aleatory in three different groups: 15 patients used a vacuum suction drain (Group I), 13 patients received quilting suture between the flap and the muscle aponeurotics wall of the abdomen, without using vacuum suction drain (Group II) and in 15 patients the fibrin sealant was used without using vacuum suction drain (Group III). The study was focused in the investigation of the seroma formation, the evaluation of the three different methods used was accomplished through an ultrasound of the abdominal wall in two different moments: On the 15th day after the surgery and on the 30th day after the surgery. RESULTS: There was a significant amount of seroma on the 15th day after the surgery in Group III. There was a significant reduction of seroma formation from the 15th day to the 30th day after the surgery in all the groups. CONCLUSION: The group with quilting suture formed less seroma in the first ultrasound (15th day after the surgery).